Implementasi Pembinaan Pendidikan Karakter dalam Membangun Kemandirian dan Disiplin Siswa SMP Negeri 34 Samarinda - Amanda Saraswati; Marwiah Marwiah; Novita Majid (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This research aims to find out the implementation of character education in building student independence and discipline at SMP Negeri 34 Samarinda. As well as obstacles to implementing character education in building student independence and discipline at SMP Negeri 34 Samarinda. Apart from that, in implementing character education in building student independence and discipline at SMP Negeri 34 Samarinda, it is necessary to approach students in order to achieve the implementation of character education in building student independence and discipline. This research uses a qualitative research approach, descriptive analysis method, with data collection techniques namely observation, interviews and documentation. . Data analysis techniques are data collection, data reduction, data presentation, and data conclusion. The research results show that SMP Negeri 34 Samarinda has implemented various character development programs, such as extracurricular activities, guidance and counseling, as well as the application of moral values ​​in learning. Students' active participation in this activity increases independence in decision making, responsibility, and courage to express opinions. Student discipline also increases through consistent application of rules and habituation of positive behavior. Teachers and school staff play an important role in enforcing discipline and setting an example. Challenges in developing character education include limited resources and variations in student discipline. Overall, character education development at SMP Negeri 34 Samarinda makes a positive contribution to student independence and discipline. Continuous support from parents and the community is needed to ensure the sustainability and effectiveness of this program. Character education development plays a role as a foundation in forming a generation that is independent, disciplined and has character.